A novel robust compression-encryption of images based on SPIHT coding and fractional-order discrete-time chaotic system. (January 2019) - Lahdir, Mourad; Hamiche, Hamid; Kassim, Sarah; Tahanout, Mohamed; Kemih, Karim; Addouche, Sid-Ali
Highlights: A novel robust compression-encryption of images by several secret keys is proposed. The proposed system is based on SPIHT coding-decoding algorithm and synchronization of chaotic maps with non-integer order. Cryptanalysis is studied through the various tests to verify the high confidentiality of the presented approach. Abstract: In this article, a novel robust compression-encryption of images based on Set partitioning in Hierarchical Trees (SPIHT) coding-decoding algorithm and synchronization of chaotic maps with non-integer order is proposed. The essential innovation in the proposed communication system is that the source image is compressed and encrypted by several secret keys. The developed transmission scheme is designed to take profit of two advantages. The first is the use of standard SPIHT coding which is an efficient and computationally very fast technique for image compression. The second is to introduce farther complexity to the cryptosystem through the use of fractional-order chaotic maps which has many advantages such as the generation of supplementary secret keys with respect to the discrete-time chaotic systems. From the obtained simulation results, we can see that the original image has been well encoded in the cipher text and retrieved with success through the chaotic signals. Further, to verify the high confidentiality of the presented cryptosystem, cryptanalysis is studied in detail through the various tests.